Biotechnologies and patent law: The case of European Union - A. I. Shcherbakova (Цифровое право, 2023)
The rapid development of biotechnologies requires taking comprehensive steps to actualise and consolidate actions. In order to introduce new technologies into life in the most rapid and appropriate way, it is imperative to establish mechanisms and instruments that meet contemporary challenges. This article presents an overview of institutional innovations of the European Union, which create favourable conditions, including for the protection of research results in the field of biotechnology. At the same time, this paper highlights new risks arising from the “information hunt” implicitly announced in the field of biotechnology. Particular attention is paid to the efforts to cooperate and harmonise approaches to the protection of intellectual rights in the biotechnology realm by the European Union and the European Patent Organisation. For the purposes of this article, one of the key factors in considering the new European Unitary Patent System through a biotechnologies perspective is the fact that the acts governing the activity contain distinctive provisions that are specific to biotechnologies. The latter manifests both in the acts introducing the System and in the current format of the Unitary Patent Court. The article states that the EU is endeavouring to provide the new institution with digital tools. Such tools are provided both at the stage of familiarising oneself with the rules and procedures of the Unified Patent Court and for performing key actions when dealing directly with a European unitary patent. However, the digitalisation of some procedures entails certain risks, primarily related to data security (e.g., sensitive development data or personal data of people involved in biotechnological developments may be made public). Once biotechnology development data are lost, there are serious consequences, both financial and scientific. In this regard, the article points out what protection formats are currently proposed and indicates that there is a need to further develop this field.